Information and Strategies for Martial Arts Instructors Working with Children Diagnosed with Attention Deficit/Hyperactivity Disorder - Eric K. Cooper (Universidad de León, 2012)
Attention Deficit//Hyperactivity Disorder is a childhood disorder on the increase in the United States, and parents are searching for additional ways to help alleviate the symptoms associated with this disorder. One of the ways parents are looking to help with ADHD is through exercise programs, including the martial arts. As more of our students are diagnosed with ADHD, it is imperative we, as martial artists and teachers, understand the nature of this disorder. Therefore, this article is intended to educate those in the martial arts about ADHD. First, an introduction about ADHD, what it is and what it is not, is offered to demystify the disorder and to insure instructors are using appropriate language and terminology. Second, current research regarding the use of the martial arts as an intervention for ADHD will be discussed. Third, the issue of confidentiality related to psychological disorders will be discussed and suggestions offered to decrease the chances of instructors breaching confidentiality. Finally, some strategies for working with children with ADHD will be offered.